REVIEWING STUDENTS’ NEEDS TOWARD CONSTRUCTIVE LEARNING ENVIRONMENT MODEL IN LEARNING LISTENING SKILL (The Journal of Educational Development, 2015)
A learning process is perceived as meaningful if it is directly or indirectly related to the experience of the environment experienced by the students. Therefore, the constructive learning environment model is considered as suitable for developing the learning process, especially in learning listening skill. This study uses R & D as the research method for assessing the suitability of the of the students’ perception witht the learning models that have already exist. As a result, this model can be used as a constructive learning environment model that is able to optimize the process of listening skill. Moreover, it can directly infuse moral values that exist in the listening process. Thus, the constructive learning environment model can address the needs of the students in learning listening skill.